The Routledge International Handbook of New Digital Practices in Galleries, Libraries, Archives, Museums and Heritage Sites - Lewi, Hannah; Smith, Wally; vom Lehn, Dirk; Cooke, Steven (Routledge International Handbooks, 2019)
Containing first-hand accounts from leading thinkers, curators, exhibition designers, historians, heritage practitioners, technologists and interaction designers, this book presents a fascinating picture of how today's cultural institutions are undergoing a transformation through innovative applications of digital technology.